PENGARUH PENAMBAHAN MALEAT ANHIDRIDA-GRAFTED-POLIPROPILENA TERHADAP SIFAT KEKUATAN BENTUR DAN PENYERAPAN AIR KOMPOSIT HIBRID PLASTIK BEKAS KEMASAN GELAS BERPENGISI SERBUK SERAT AMPAS TEBU DAN SERBUK SERAT KACA - Castiqliana; Silvia; Halimatuddahliana (Jurnal Teknik Kimia USU, 2016)
A study on wasted polypropylene/modified bagasse fiber flour/E-type glass fiber flour with maleic anhydride-g-polypropylene addition hybrid composite was performed and its impact properties and water absorption ability was analyzed. Glass fiber flour and maleic anhydride-g-polypropylene compositions were made constant at 10 wt.% and 2 wt.% respectively, and modified bagasse fiber flour composition was varied from 10-40 wt.%. Surface modification on bagasse flour with 1% sodium hydroxide was also conducted. The composites were prepared in an extruder. The result showed that the maximum impact strength of 46,6 J/cm2 was obtained in addition of modified bagasse fiber flour of 30 wt.%. Impact strength result was also supported by Scanning Electron Microscopy analysis. Water absorption test showed that the increase of modified bagasse fiber flour content resulted to the increase of water absorbance and composites with maleic anhydride-g-polypropylene addition had lower ability to absorb water when compared to composite without maleic anhydride-g-polypropylene addition in the same fillers content.